Maternal and Fetal Outcomes in Obesity Complicated Pregnancies - Umber Asad, Saima Khan, Saima Zulfiqar, Rubab Munawar, Shamim Akhtar, Zara Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Obesity in reproductive age women is growing to epidemic proportions causing adverse perinatal outcomes and various pregnancy complications. Pregnant women with obesity pose risks for child and maternal health in terms of intrapartum, antenatal, postpartum and neonatal complications. The current study aim was to find the maternal and fetal outcomes in complicated pregnancies of obese women. Methodology: This cross-sectional study was conducted on 164 pregnant women in the Department of Obstetrics and Gynecology, Lahore General Hospital, from April 2021 to March 2022. Prior to study conduction, ethical approval was granted from the institution research and ethical committee. Informed consent was taken from each individual. Based on BMI index for pre-pregnancy, participants were categorized as normal weight (19-25 kg/m2), overweight (25-30 kg/m2), and obese (≥30 kg/m2). All the pregnant women with gestational age of 20 weeks who were willing to participate were enrolled. Underweight women with previous anomaly babies and miscarriage were excluded. Maternal and fetal outcomes were recorded. SPSS version 25 was used for data analysis. Results: The overall mean age of the participants was 26.4±3.61 years. Based on BMI (kg/m2), the participants were distributed as follows; 26.8% (n=44) of normal weight (19-25 kg/m2), 28.1% (n=46) of overweight (25.0 - 30 Kg/m2), and 45.1% (n=74) of obese ((≥30 kg/m2). Majority of overweight and obese women were ≥ 30 years old. Diabetes before pregnancy was strongly related to obesity (16.3%, p<0.0001). Lower weight gain (10.3 ± 6.9 Kg) were seen in obese pregnant women. Comparing to the normal weight women, overweight and obese women physical exercise more often (p=0.01). Obese women were more susceptible to the risk of developing hyperglycemic disturbance (OR= 6.2; 3-10.5), hypertension (OR=6.8, 3.0-15.5), and HbA1c ≥ 6. 5 % (OR=3.5; 1.1-10.8). Longer hospitalization (4.1 ± 2.9 days) was seen in infants born to obese mother (p=0.005). The gestational age babies born from obese mother had a proportion of (14.6%) (p=0.022) with higher abdominal and thoracic circumference (30.7 ± 2.1 cm) and (32.8 ± 1.9 cm) respectively. Conclusion: Our study concluded that adverse perinatal outcomes and pregnancy complications could be caused by obesity in pregnant women. Obese women were more susceptible to increase risk of developing gestational diabetes mellitus, postpartum complications, pregnancy related hypertensive disorders, pre-eclampsia, preterm birth, cesarean section, and longer hospital stay. The importance of weight status before and during pregnancy should be identified to have adequate treatment. Keywords: Pregnancy, Maternal outcomes, Fetal outcomes, Obesity